Aporte de “amistad con los amigos de la calle” al bienestar emocional en adultos mayores: el caso de la comunidad de Sant Egidio Perú - Laurente Luna, Jessica Roxana (2023)
In Peru, there are more than 4 million people over the age of 60. Within this population segment, there is a high number of elderly individuals (EIs) who have not been included in any public state report and are in a situation of poverty and extreme poverty, living alone in small spaces or in complete destitution on the streets of the city. In this context, the Sant' Egidio Peru community, a Catholic lay organization from civil society, has been running the “Friendship with the Street Friends” service in the Montserrat neighborhood in the Cercado de Lima district since 2008. Through this service, program volunteers provide social assistance and support services to EIs in a welcoming environment that facilitates the formation of friendships. The qualitative research used four information collection techniques: semi-structured interviews (individual and group), an open biographical interview, participant observation, and document review. Four units of analysis were included: elderly individuals using the service, volunteers, the service director, and public officials. The study analyzed how the Sant' Egidio Peru service has positively contributed to the emotional well-being of EIs. The research found that the service has become a welcoming environment where EIs establish friendships that dignify their lives and strengthen them in exercising their rights. This is essential for this human group to achieve active aging and optimal quality of life given the state's deficiencies in guaranteeing their quality of life. The study proposes recommendations from social management for both public and private organizations to enhance policies and plans that prioritize EIs in general.